STATE AND RELIGION IN SAINT AUGUSTINE: A REFLECTION FROM THE DONATIST CONFLICT - Vahl, Matheus Jeske (2023)
Set in North Africa during late antiquity, St. Augustine's political thought is not systematized in a theoretical body of works. It is the result of his reflection on concrete problems such as the legitimacy of state intervention in religious quarrels such as the conflict between Catholics and Donatists. The Augustinian vision of the State foresees a Christian engagement in the political sphere, not in the sense of medieval theocracy, but with a view to its moral purification. He believes that he must intervene in the private sphere of faith to avoid extreme violence, but he does not believe that his institutions can be just if they are not guided by the true piety of the Christian faith. For Augustine, one of the reasons for Rome's social decay is its belief in false narratives that did not lead citizens to authentic moral growth, in which in his view the Church can and should collaborate with the State.